INTERNAL AND EXTERNAL HARMONY AMONG THE FAITHFUL: INTERPRETATION OF ĀLI ‘IMRĀN: 103 AND AL-SHŪRĀ: 13 - Dika Purnama Aulia Rohma (TAFASIR: Journal of Quranic Studies, 2025)
This paper aims to explore the values of unity in the Qur'an to build internal and external harmony among religious communities. This study uses a library method with a thematic interpretation approach to QS. Āli ‘Imrān [3]:103 and QS. al-Shūrā [42]:13. The findings of this study indicate that these two verses provide a complete foundation for achieving harmony. Internally, QS. Āli ‘Imrān [3]: 103 emphasises a good relationship with Allah through the Qur'an, a good relationship with other creatures through ukhuwah Islamiyah (Islamic brotherhood), and avoiding fanaticism. Externally, QS. al-Shūrā [42]: 13 teaches harmony by practising one's respective religious teachings, building ukhuwah basyariyah and wathaniyah, and conveying the truth without coercion.